2010
DOI: 10.1164/rccm.200905-0794oc
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Monoxide Pollution Promotes Cardiac Remodeling and Ventricular Arrhythmia in Healthy Rats

Abstract: Chronic CO exposure promotes a pathological phenotype of cardiomyocytes in the absence of underlying cardiomyopathy. The less severe phenotype in vivo suggests a role for compensatory mechanisms. Arrhythmia propensity may derive from intracellular Ca(2+) overload.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(90 citation statements)
references
References 56 publications
5
83
0
2
Order By: Relevance
“…The chief mechanisms underlying the ability of CO to scavenge ROS have yet to be explored. CO could appear to act via oxidative stress since it reduced the activity of several antioxidant enzymes [30]. This effect on antioxidant enzymes, however, is not always observed [18].…”
Section: Discussionmentioning
confidence: 98%
“…The chief mechanisms underlying the ability of CO to scavenge ROS have yet to be explored. CO could appear to act via oxidative stress since it reduced the activity of several antioxidant enzymes [30]. This effect on antioxidant enzymes, however, is not always observed [18].…”
Section: Discussionmentioning
confidence: 98%
“…We propose that ranolazine or related drugs that act by inhibiting the late Na 1 current may have therapeutic benefit in such cases. In summary, the present study has identified the molecular basis for the proarrhythmic effects of acute CO exposure, which is distinct from chronic CO-induced remodeling of cardiac function (6) and is increasingly recognized as a common phenomenon of clinical importance. We also provide compelling evidence that CO exposure in vivo can, particularly during additional stress, such as increased b adrenergic stimulation, lead to fatal arrhythmias.…”
Section: Cardiac Namentioning
confidence: 89%
“…Chronic exposure to moderate (30-200 ppm) CO can induce myocardial injury and fibrosis (3)(4)(5)(6). However, acute environmental (e.g., road traffic) (7) exposure to CO (up to 500 ppm) is associated with arrhythmias and an increased risk of sudden death (3,8), particularly in patients with existing cardiac conditions (9,10).…”
mentioning
confidence: 99%
“…Andre and colleagues exposed Wistar rats to either filtered air (CO , 1 ppm) or air enriched with CO (30 ppm with five peaks of 100 ppm per 24-h period) for 4 weeks and evaluated the myocardial function by echocardiography and EKG and in vitro by measuring the excitationcontraction coupling of single left ventricular cardiomyocytes (40). They found that CO caused fibrosis in the left ventricle and a small reduction in cardiac function and increased the number of arrhythmias in vivo.…”
Section: Carbon Monoxidementioning
confidence: 99%